Personalized epigenetics - Tollefsbol, Trygve O. (Amsterdam : Elsevier Ltd., 2015)
Personalized Epigenetics discusses the core translatability of epigenetics to health management of individuals who have unique variations in their epigenetic signatures that can guide both disorder and disease prevention and therapy. The book details inter-individual variability in the major epigenetic process in humans consisting of DNA methylation, histone modifications, and noncoding RNA, and the diagnostic, prognostic, and therapeutic potential of the field, it also reviews the impact of the environment on epigenetic variations among individuals and the role of pharmacology and drug de.
Chapter 1 - Epigenetics of Personalized Medicine -- Chapter 2 - Interindividual Variability of DNA Methylation -- Chapter 3 - Differences in Histone Modifications Between Individuals -- Chapter 4 - Individual Noncoding RNA Variations: Their Role in Shaping and Maintaining the Epigenetic Landscape -- Chapter 5 - Personalized Epigenetics: Analysis and Interpretation of DNA Methylation Variation -- Chapter 6 - Computational Methods in Epigenetics -- Chapter 7 - Epigenetic Biomarkers in Personalized Medicine -- Chapter 8 - Epigenetic Fingerprint -- Chapter 9 - Epigenetics of Personalized Toxicology -- Chapter 10 - Environmental Contaminants and Their Relationship to the Epigenome -- Chapter 11 - Nutriepigenomics: Personalized Nutrition Meets Epigenetics -- Chapter 12 - Personalized Pharmacoepigenomics -- Chapter 13 - Personalized Medicine and Epigenetic Drug Development -- Chapter 14 - Epigenetics and Personalized Pain Management -- Chapter 15 - Understanding Interindividual Epigenetic Variations in Obesity and Its Management -- Chapter 16 - Epigenetic Modifications of miRNAs in Cancer -- Chapter 17 - Managing Autoimmune Disorders through Personalized Epigenetic Approaches -- Chapter 18 - Cardiovascular Diseases and Personalized Epigenetics -- Chapter 19 - Future Challenges and Prospects for Personalized Epigenetics.
Includes bibliographical references and index.
Vendor-supplied metadata.
Elsevier
Keywords: Epigenetics; Epigenomics; SCIENCE / Life Sciences / Biochemistry; Epigenesis, Genetic; Epigenetics; Genetic regulation; Epigenetics; Electronic books; Electronic books